ANALISIS PREFERENSI, POLA KONSUMSI, DAN PERMINTAAN CABAI HIJAU TINGKAT RUMAH TANGGA DI KOTA BANDAR LAMPUNG - Pratiwi, Sisilia Putri; Prasmatiwi, Fembriarti Erry; Adawiyah, Rabiatul (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
The purpose of this study was to analyze preferences, consumption patterns and factors that influence household level consumption of green chilies in Bandar Lampung City.  The research method used is the survey method.  Data collection was carried out in November – December 2023 with a total of 70 household sample. Sampling was carried out in four sub-districts, namely Sukarame sub-district, Way dadi sub-district, Pesawahan sub-district, and Gunung Mas sub-district.  The data analysis used is conjoint analysis, descriptive analysis, and multiple linear regression analysis.  The results of the research show that household preferences in Bandar Lampung City for green chilies are spicy, lowest price (<Rp20.000), fresh, bright green, and curly green chilies.  Households consume chilies in the form of chili sauce or mixed dishes with an average weekly consumption per capita of 0,019 kg.  Households also consume curly green chilies.  Purchases are only made once a month at traditional markets.  The average household consumes green chilies only 1-2 times a month. Factors that have a significant influence on household demand for green chilies in Bandar Lampung City are the price of green chilies and the number of household members. Key words: chili, consumption pattern, demand, preference